Therapeutic molecules for multiple human diseases identified from pigeon pea (Cajanus cajan L. Millsp.) through GCâMS and molecular docking - Deepu Mathew; Lidiya John P.; Manila T.M.; Divyasree P.; Sandhya Rajan V.T.K. (Food Science and Human Wellness)
Molecular mechanism behind the therapeutic potential of pigeon pea over the human diseases such as rheumatoid arthritis, breast cancer, type II diabetes, malaria, measles and sickle cell disease were revealed through docking of GCâMS identified phyto-compound ligands with candidate disease proteins. Of the 242 ligands, three dimensional structures of 47 compounds had to be drawn using ChemSketch and the remaining structures were retrieved from PubChem and docked with the active sites of candidate proteins. The molecules identified through docking were further subjected to ADMET analysis and promising drug candidates were identified for each disease. This paper presents a precise account of the chemoprofile of pigeon pea leaves, stems and seeds, interaction of these molecules with target proteins and suggests 26 highly potential molecules which are drug candidates for multiple human diseases. Pigeon pea seeds are especially proven as invaluable source for therapeutic molecules. Keywords: Breast cancer, Drug discovery, Herbal medicine, In silico, Malaria, Measles, Phyto-compounds, Rheumatoid arthritis, Sickle cell disease, Type II diabetes